2007
DOI: 10.1002/mc.20372
|View full text |Cite
|
Sign up to set email alerts
|

Independent activation of Akt and NF‐kappaB pathways and their role in resistance to TNF‐α mediated cytotoxicity in gliomas

Abstract: Tumor associated macrophages (TAMs) constitute a substantial mass in gliomas. The activated macrophages secrete various cytokines that affect diverse functions of tumors. The aim of this study was to elucidate the role of Akt and NF-kappaB pathways in resistance to TNF-alpha mediated cell death in human gliomas using monolayers and multicellular spheroids (MCS) as in vitro models. Akt and NF-kappaB are constitutively expressed and intimately involved in progression of gliomas. The activation of these pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Supporting our data, a previous report has shown that NF-kB is activated in glioma spheroids, becoming relatively resistant to TNF-a [Sudheerkumar et al, 2008]. Although not studied, IAPs could mediate this resistance, since it is well known that they can also repress apoptosis induced by TNF-a [Uren et al, 1996].…”
Section: Discussionsupporting
confidence: 82%
“…Supporting our data, a previous report has shown that NF-kB is activated in glioma spheroids, becoming relatively resistant to TNF-a [Sudheerkumar et al, 2008]. Although not studied, IAPs could mediate this resistance, since it is well known that they can also repress apoptosis induced by TNF-a [Uren et al, 1996].…”
Section: Discussionsupporting
confidence: 82%
“…However, the involvement of the PI3K/Akt pathway in NF-κB activation is a cell- and tissue-specific event. It has been confirmed that TNF-α-induced NF-κB activation is independent of the PI3K/Akt pathway in human glioma cell lines 23. Shao et al suggested that radiation-induced NF-κB activation is independent of Akt activation in parental cancer cells 24.…”
Section: Discussionmentioning
confidence: 94%
“…Despite studies reporting the interdependence and cross-talk between Akt and NF-κB [26], phosphorylation of Akt by PI3K pathway independent of NF-κB is also well evidenced [30-33]. Similarly, while several reports strongly correlate the involvement of NF-κB in Cyclin D1 regulation [30], there are reports which clearly demonstrate the transcription of Cyclin D1, independent of NF-κB, in cell lines including A549 [32,4]. The protein level expression of Cyclin D1 in A549 was low compared to that in H1299 cells at all the concentrations studied (Fig.…”
Section: Resultsmentioning
confidence: 99%